The Analysis of the Competitiveness of Romanian Exports Using Constant Market Share Method - Paul Clipa (CES Working Papers, 2012)
Romanian exports represented, lately, a major engine of economic growth. However, only a deep analysis of these can reveal the factors that contributed to their competitiveness. Indicators that capture the changes in market shares provide the most accurate picture of the concept of competitiveness of exports. They are found in the literature as a method of constant market share analysis, method developed by H. Tyszyinski in 1951.
Keywords: F14; F15; F16; F40; 330; exports; competitiveness; market share; structural effect; competitiveness effect Romania